The Influence of Social Media, Price, and E-Word of Mouth on Purchasing Decisions at Florist Flower Shops - Maharani, Ni Putu Ayu Putri; Widnyani, Ni Made; Aristayudha, A A Ngurah Bagus (Westscience Press, 2024)
The study aims to determine how Social Media, Price, and E-Word of Mouth influence Purchase Decisions, particularly in flower shops in Denpasar city. This research uses a quantitative approach. Sampling was done using Nonprobability Sampling with Random Sampling, resulting in a sample size of 100 respondents. Data were processed using SPSS version 26 software. The analysis method used was multiple linear regression analysis, with respondents being customers of flower shops in Denpasar city. The research instrument was a questionnaire. Statistical analysis methods used in this study include validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t-tests, F-tests, and correlation tests. The results showed that the t-value for social media was 6.123, which is greater than the t-table value of 1.66088, indicating that social media affects purchase decisions. The t-value for price was 2.829, greater than the t-table value of 1.66088, indicating that price affects purchase decisions. The t-value for E-WOM was 3.734, greater than the t-table value of 1.66088, indicating that E-WOM affects purchase decisions. The F-test value was 91.937, which is greater than the F-table value of 2.699, indicating that social media, price, and E-WOM simultaneously influence purchase decisions.